Generation Alpha’s Perception of Arabic in the Era of Globalization: A Psycho-Sociolinguistic Study - Aziz, Mushlih Abdul; Setiyawan, Agung; Husaini, Busyro; Pratama, Budi (AL-TA'RIB : Jurnal Ilmiah Program Studi Pendidikan Bahasa Arab IAIN Palangka Raya, 2025)
In an era of globalization marked by developments in technology and cross-cultural communication, Arabic faces significant challenges in maintaining its relevance and appeal among the Alpha generation. The generation born between 2010-2024 is the first generation that has been thoroughly exposed to digital technology from birth, with characteristics that are very different from previous generations. This research aims to analyze the Alpha Generation's perception of Arabic through a psycho-sociolinguistic approach, which examines psychological (interest, motivation and attitudes) and social (influence of the environment, media and global culture) aspects in learning Arabic. This research uses a qualitative method with a descriptive-analytical approach. Data was collected through in-depth interviews and observations of Generation Alpha students in an Islamic-based education environment. The research results show that the Alpha generation's perception of Arabic is influenced by three main factors: digital exposure, individual psychological constructs, and socio-cultural context. Most of the Alpha Generation have motivation to learn Arabic which is influenced by religious factors, but negative perceptions of the difficulty of this language often reduce their interest. This research is expected to provide new theoretical contributions in understanding the dynamics of language perception in the digital native generation and practical implications for the development of more contextual and innovative Arabic language teaching methods.